People's Republic of China : Financial System Stability Assessment. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
This report discusses the IMF/World Bank Financial Sector Assessment Program (FSAP) exercise for China undertaken during June-December 2010. The assessment concluded that reforms in China have progressed well in moving toward a more commercially oriented financial system. Despite success and rapid growth, China's financial sector is confronting several near-term risks, structural challenges, and policy-induced distortions. A properly composed and timely implemented set of reforms would help address these challenges. A framework to resolve weak financial institutions on a timely basis is also needed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet